Drones an illustrated guide to the unmanned aircraft that are filling our skies - Dougherty, Martin J. (Amber Books, 2015)
From drones the size of a fingertip to drones that can carry soldiers, from rotorcraft to submersible drones, this book expertly examines these complex autonomous vehicles.